The Necessity of Teaching Diabetic Patients the Correct way of Insulin Administration: A Clinical Trial to Improve Glycemic Control - Al- Lehibi, Khalid Ibrahim; Abdul Raheem, Yousif; Hussein, Ibtisam Shilbah (AL-Kindy College Medical Journal, 2012)
Background: It is important to achieve good glycemic control to avoid long-term diabetic complications. It has been largely debated about the role of correct way of insulin administration to get the desired glycemic control. Objective: To evaluate the effect of teaching diabetic patients who are on insulin therapy the correct way of injecting insulin and its effect on glycemic control. Methods: A non randomized clinical trial with 820 diabetic patients on insulin therapy on whom A1 c estimation was performed before and after three months of teaching them the right injection technique. Results : Sixty seven patients (8.17%) had A1 c 6.5% before they were enrolled in the study while the majority (753 patents, 91.82%) had A1 c 6.5% and the last group showed the best benefit of teaching them the correct way of injection when compared with first group (P= 0.0001). Also patient with age 20-40years showed the best results (P=0.0001), while the poorest results were observed in those aged 40 years and above. Conclusion: Teaching patients the right injection technique is important to achieve good glycemic control in those who already had poor one.